LUklbXJvd0c2Iy9JK21vZHVsZW5hbWVHNiJJLFR5cGVzZXR0aW5nR0koX3N5c2xpYkdGJzYjLUkjbWlHRiQ2I1EhRic= # How can I obtain ne(X), ni(X) and np(X) in term of phi(X) from the following Eqs. (using the following B.C.) to convert the last Eq. as (diff(phi(X), X))^2+2*F(phi) = 0. # BC: ne,ni,np -->1, uex,uey,uix,uiy,upx,upy-->0, phi-->0 at infinities restart; -M*(diff(ne(X), X))+diff(ne(X)*uex(X),X)=0; -M*(diff(uey(X), X))+uex(X)*diff(uey(X), X)-R1*uex(X)=0; -M*(diff(uex(X), X))+uex(X)*diff(uex(X), X)+R1*uey(X)-mu1*diff(phi(X),X)+mu1*(1/ne(X))*diff(ne(X),X)=0; -M*(diff(ni(X), X))+diff(ni(X)*uix(X),X)=0; -M*(diff(uiy(X), X))+uix(X)*diff(uiy(X), X)+R2*uix(X)=0; -M*(diff(uix(X), X))+uix(X)*diff(uix(X), X)-R2*uiy(X)+mu2*diff(phi(X),X)+T2*mu2*(1/ni(X))*diff(ni(X),X)=0; -M*(diff(np(X), X))+diff(np(X)*upx(X),X)=0; -M*(diff(upy(X), X))+upx(X)*diff(upy(X), X)+R3*upx(X)=0; -M*(diff(upx(X), X))+upx(X)*diff(upx(X), X)-R3*upy(X)+T3*mu3*diff(phi(X),X)+T3*mu3*(1/np(X))*diff(np(X),X)=0; diff(phi(X),X\$2)-(1+delta)*ne(X)+delta*np(X)+ni(X)=0; JSFH JSFH